Distribution Patterns Of Educational Assistance (Scholarships) In Improving Student Academic Achievement (Case Study Of The Dharmasraya National Amil Zakat Agency) - Muhammad Deni Putra; Ronaldi Ronaldi (IAIN Batusangkar, 2021)
The distribution of zakat can be carried out in various patterns, depending on the managerial policy of the agency or zakat institution concerned. Sometimes it is channeled directly to mustahiik with a consumptive pattern and sometimes it is realized in a productive form or by providing capital or zakat can be developed with an investment pattern. The purpose of this study is to find out and explain how the pattern of determining recipients and determining the amount of educational assistance (scholarships) for students at BAZNAS, Dharmasraya Regency. The type of research that the author does is field research (field research). The method used is descriptive qualitative. The pattern of determining recipients and the pattern of determining the amount of educational assistance (scholarships) for students at BAZNAS, Dharmasraya Regency, namely: that the determination of recipients must meet general and special requirements, after completing the file, BAZNAS will make a selection which is done by: administration, written test , interviews and surveys to the field after being eligible to be determined as recipients of scholarship assistance, it is necessary to determine the decision of the leadership of BAZNAS Dharmasraya Regency regarding the determination of the names of the scholarship recipients. And in determining the amount of assistance, it has been regulated in the Work Plan and Budget (RKAT) of BAZNAS Dharmasraya Regency.